2019
DOI: 10.1038/s41386-018-0308-1
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Gpr39, a G-protein coupled receptor associated with alcohol use in non-human primates, curbs ethanol intake in mice

Abstract: Alcohol use disorder (AUD) is a chronic condition with devastating health and socioeconomic effects. Still, pharmacotherapies to treat AUD are scarce. In a prior study aimed at identifying novel AUD therapeutic targets, we investigated the DNA methylome of the nucleus accumbens core (NAcc) of rhesus macaques after chronic alcohol use. The G-protein coupled receptor 39 (GPR39) gene was hypermethylated and its expression downregulated in heavy alcohol drinking macaques. GPR39 encodes a Zn 2+-binding metabotropic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 78 publications
2
23
0
Order By: Relevance
“…Our own GPR39 protein expression studies using rodent depression models corroborate the existence and the functional importance of the receptor in the murine hippocampus [73,74]. Recent findings from another group showed alterations of GPR39 protein levels in the mouse nucleus accumbens to be linked to alcohol consumption [75]. Therefore, it is highly probable that the GPR39 receptor participates in neurotransmission in at least three subcortical structures responsible for mood, memory and decisionmaking.…”
Section: Gpr39 Expression Pattern In the Cnssupporting
confidence: 68%
“…Our own GPR39 protein expression studies using rodent depression models corroborate the existence and the functional importance of the receptor in the murine hippocampus [73,74]. Recent findings from another group showed alterations of GPR39 protein levels in the mouse nucleus accumbens to be linked to alcohol consumption [75]. Therefore, it is highly probable that the GPR39 receptor participates in neurotransmission in at least three subcortical structures responsible for mood, memory and decisionmaking.…”
Section: Gpr39 Expression Pattern In the Cnssupporting
confidence: 68%
“…Later, it has been shown to activate all GPR39 inducible pathways [ 35 ]. Since its discovery, TC-G 1008 has proven to be a potent agonist and a very valuable tool in characterizing the physiological functions and therapeutic potential of GPR39 activation, published by a number of studies to date [ 30 , 31 , 32 , 35 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 ]. However, most studies have not verified their findings in GPR39 −/− settings, which would be critical in order to confirm that the observed effects are indeed GPR39-dependent.…”
Section: Ligands Of Gpr39mentioning
confidence: 99%
“…Intriguingly, recently GPR39 agonists were studied for the treatment of alcohol use disorder [ 61 ]. GPR39 was found to be hypermethylated and downregulated after chronic alcohol use in non-human primates, rhesus macaques.…”
Section: Physiological Functions Of Gpr39mentioning
confidence: 99%
See 1 more Smart Citation
“…Oral administration of a GPR39 agonist, TC-G1008, inhibited liver injury marker glutamic-pyruvic transaminase expression and reduced hepatic cell necrosis in concanavalin A-induced hepatitis liver in mice[ 93 ]. Another study showed that an acute dose of TC-G1008 reduced ethanol intake in mice without affecting total fluid intake[ 94 ]. GPR40 deficiency was associated with hepatic inflammation and steatosis in low-fat diet-fed mice[ 95 ].…”
Section: Gpcr-based Therapies For Liver Diseasesmentioning
confidence: 99%